Improvement of Photosynthesis Through Photoprotection in Wheat and Rice - Foo, Chuan Ching (2019)
Photosynthesis is the light-driven process fundamental to life. Although widely studied, this process is still not well understood and there is a need to address the gap in the photosynthetic response of crop canopies towards the fluctuating light environment. Wheat and rice are the top two important cereal crops feeding the global population. The manipulation of a Photosystem II subunit S photoprotective gene, PsbS, in these crops would allow further understanding of how they respond to the canopy light environment in terms of non-photochemical quenching (NPQ). Spring wheat (cv ‘Fielder’) was transformed successfully to overexpress rice PsbS (Os01g64960). However, they failed to maintain the phenotype to T2 generation and no wheat plant homozygous for rice PsbS was obtained for further studies. Wheat canopy NPQ studies were made on a subset of genetically diverse (PSTails) wheat population. NPQ capacity and variations were greater at the bottom of the wheat canopy. In the screening of large wheat populations, a new parameter NPQ(T) proved useful as NPQ(T) midday measurements correlated negatively to total radiation use efficiency and biomass, and to some extent, correlated positively to grain yield. NPQ and its protective ability were studied at a rice canopy scale using established rice (cv ‘Kaybonnet’) PsbS overexpressor and RNAi lines. PsbS levels in rice can be overexpressed to benefit the crop canopies by reducing the risk of photoinactivation. Consistent with the results from wheat canopy study, the bottom of rice canopies also showed higher NPQ capacity and phototolerance. PsbS is known to play a photoprotective role but was recently suggested to control stomatal pore opening in tobacco (Głowacka et al., 2018). An experiment carried out under controlled environment showed that PsbS is not involved in stomatal regulation. However, there was some evidence that under a mild water deficit, rice overexpressing PsbS have slightly improved water use efficiency. Another study using nitrogen-fixing bacteria in rice (cv ‘Valencia) showed that under no nitrogen treatment, there was some indication of improved photosynthesis (not significant). It was the first time that a 100% colonization of rice seedlings with Gd was observed.